ChemInform Abstract: Palladium‐Catalyzed Carbonylative Multicomponent Synthesis of Functionalized Benzimidazothiazoles. Issue 36 (August 2016) - Veltri, Lucia; Grasso, Giuseppe; Rizzi, Rosanna; Mancuso, Raffaella; Gabriele, Bartolo
Abstract: by domino oxidative aminocarbonylation/heterocyclization of propynylthiobenzimidazolium bromides with various amines and CO